On the Blue Comet - Wells, Rosemary; Ibatoulline, Bagram (Somerville, Mass. : Candlewick Press, 2010)
When Oscar Ogilvie's father must look for work in California, Oscar is left with his aunt, where he befriends a drifter, witnesses a bank robbery, and is catapulted onto a train that takes him to a different time and place.
Sequoyah Nominee 2013
730
Keywords: Space and time -- Fiction; Railroads -- Fiction; Single-parent families -- Fiction; Great Depression, 1929-1939 -- Fiction; Adventure fiction; California -- History -- Fiction; Illinois -- History -- Fiction